Study on the aesthetics of Nahjolbalaghe 224 sermon - ATEFEH rahmani; ahmad pashazanous (مطالعات زبانی و بلاغی)
Aesthetic reviews examine the analysis of literary texts on the basis of their artistic and technical principles.  In addition to music and structure, following method evaluates literary texts based on the four principles of sense, imagery, style and being spiritual or abstract. Aesthetic reviews of literary works have closer relation to the nature of literature and understanding its secrets, because they derive from the origin of literature and regulate their principles and rules in accordance with it. Common features of the studied sermons are as follows: deep concepts and semantic coherence, emotional power and dynamism due to the components of true affection, fluent expressing without complicacy  due to using imagination with aim of deepening the meaning and aesthetic, coherent style, harmonization of music and rhythm of the words with meaning and emotion that prevents the artificial array in these sermons, coordination of the word choice with voice and sentence structure, Eloquence of words, harmonization and coordination of words with meaning and compatibility of the four literary elements.